The Effect of Blood Flow Restriction Exercise on Angiogenesis-Related Factors in Skeletal Muscle Among Healthy Adults: A Systematic Review and Meta-Analysis - Li, Shuoqi; Li, Shiming; Wang, Lifeng; Quan, Helong; Yu, Wenbing; Li, Ting; Li, Wei (Frontiers in Physiology, 2022)
Background Blood flow restriction (BFR) exercise may be a potential exercise program to promote angiogenesis. This review aims to compare the effects of exercise with and without BFR on angiogenesis-related factors in skeletal muscle among healthy adults. Methodology Searches were made in Web of Science, Scopus, PubMed, and EBSCO databases from January 2001 to June 2021. Studies were screened, quality was evaluated, and data were extracted. The review protocol was registered at PROSPERO (PROSPERO registration number: CRD42021261367). Standardized mean differences (SMD) of vascular endothelial growth factor (VEGF), vascular endothelial growth factor receptor 2 (VEGFR-2), hypoxia inducible factor 1α (HIF-1α), peroxisome proliferator-activated receptorγcoactivator-1α (PGC-1α) and endothelial nitric oxide synthase (eNOS) were analyzed using Revman 5.4 software with a 95% confidence interval (95% CI). Results Ten studies fulfilled the inclusion criteria with a total of 75 participants for BFR group and 77 for CON group. BFR exercise elicits greater expression of VEGF (heterogeneity test, P = 0.09, I2 = 44%; SMD, 0.93 [0.38, 1.48], P < 0.05), VEGFR-2 (heterogeneity test, P = 0.81, I2 = 0%; SMD, 0.64 [0.08, 1.21], P < 0.05), HIF-1α (heterogeneity test, P = 0.67, I2 = 0%; SMD, 0.43 [0.03, 0.82], P < 0.05), PGC-1α (heterogeneity test, P = 0.02, I2 = 54%; SMD, 0.74 [0.21, 1.28], P < 0.05) and eNOS (heterogeneity test, P = 0.88, I2 = 0%; SMD, 0.60 [0.04, 1.17], P < 0.05) mRNA than non-BFR exercise. In the sub-group analysis, resistance exercise with BFR elicits greater expression of VEGF (heterogeneity test, P = 0.36, I2 = 6%; SMD, 1.66 [0.97, 2.35], P < 0.05) and HIF-1α (heterogeneity test, P = 0.56, I2 = 0%; SMD, 0.51 [0.01, 1.02], P < 0.05) mRNA than aerobic exercise with BFR. Conclusion Exercise with BFR elicited more angiogenesis-related factors mRNA expression than exercise without BFR, but not VEGF and PGC-1α protein expression. Therefore, BFR training may be a potential training program to improve vascular function. Systematic Review Registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42021261367].